A variation analysis on the ADNMT sequence procedure in resident people at the Cundiboyacense region (2016)
The use of mitochondrial DNA (mtDNA) has become an important tool for the resolution of forensic cases such as in identification of human remains, samples of hair on sex crimes and homicides. With increasing population studies in the field of mtDNA and consequently an increase in the database allows the Genetics Group have a more robust system of discrimination in human identification of biological traces or forensic interest. In this work a genetic-population study of individuals of Cundinamarca and Boyacá departments analyzing, a sample of 100 individuals obtaining the variation of the sequences of the regions HVI and HVII. In total 78 different haplotypes were found in the 100 individuals analyzed, leading to genetic diversity (as Tajima F, 1989) of 98.89% (0.9889), having a high discrimination power in cases of forensic genetics area and helps us to expand the database of mtDNA for forensic purposes.